Development of an Artificial Nose Using 3D Printing Technology for Patients with Tumors - Abdullah, Abdul Halim; Bolhassan, Nazira; Mazlan, Muhammad Hazli; Bahari, Abdul Rahim; Marwan, Shahrul Hisyam (ijoe, 2024)
A prosthetic nose is an option where the patient can gain an artificial organ for aesthetics. Thus, this study includes the 3D scan and reconstruction of the 3D model of an artificial nose and analyzes different material properties, which are thermoplastic polyurethane (TPU), thermoplastic elastomer (TPE), and nylon 6 (PA). This research aims to fabricate an artificial nose model using 3D printing technology. A 3D scanner can scan the human head before reconstructing the nose. The analysis of different materials on the artificial nose model is to determine the appropriate material for the artificial nose to fit perfectly into the patient’s face. The artificial nose will use TPU material with a deformation value of 0.00413mm and a maximum stress value of 0.4930 MPa. This prosthesis nose enables people to interact in their social and family lives, making them happier and more comfortable.